Paradigm of integration-interconnection: M. Amin Abdullah and Mehdi Golshani's perspective - Fian, Khafifatul; Hidayat, Fahri (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
The existence of a monodisciplinary approach leaves no room for discussion between the sciences. There needs to be an interconnection and integration approach so that some sciences can reveal ideas to solve the problems faced. The focus of this research is on the comparison of the thoughts of M. Amin Abdullah and Mehdi Golshani on the integration of scientific interconnections. This research is library research through data collection techniques by searching for sources, either articles, books, or other sources relevant to the topic of discussion. After collecting the data, it is selected, analyzed, and conclusions formulated. The results showed that Mehdi Golshani supported the integration of scientific interconnection, but only for religion and science. In contrast to the perspective of M. Amin Abdullah, who created the idea of interconnection between religious science and general science, not only science was described through spider webs. M. Amin Abdullah assumes that religion and general science must be open to each other, even though each science has characteristics. With openness, it can create space for discussion so that what is debated as a problem can be criticized to produce a more comprehensive opinion.